2014
DOI: 10.7314/apjcp.2014.15.10.4245
|View full text |Cite
|
Sign up to set email alerts
|

miR-186 Regulates Glycolysis through Glut1 During the Formation of Cancer-associated Fibroblasts

Abstract: Emerging evidence has suggested that glycolysis is enhanced in cancer-associated fibroblasts (CAF), and miR-186 is downregulated during the CAF formation. However, it is not clear whether miR-186 is involved in the regulation of glycolysis and what the role of miR-186 plays during the CAF formation. In this study, quantitative PCR analysises show miR-186 is downregulated during the CAF formation. Moreover, miR-186 targets the 3' UTR of Glut1, and its overexpression results in the degradation of Glut1 mRNA, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Zhang et al (13) revealed that miR-186 may be a diagnostic and predictive factor for pancreatic ductal adenocarcinoma, and it affects the proliferation and invasion of tumor cells (13). Lee et al (12) demonstrated that upregulated miR-186 is associated with the proliferation of human lung fibroblasts and Sun et al (11) indicated that miR-186 regulates the formation of tumor-related fibroblasts. In addition, Cui et al (10) revealed that miR-186 inhibits the proliferation and metastasis of non-small-cell lung carcinoma cells by targeting Rock1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (13) revealed that miR-186 may be a diagnostic and predictive factor for pancreatic ductal adenocarcinoma, and it affects the proliferation and invasion of tumor cells (13). Lee et al (12) demonstrated that upregulated miR-186 is associated with the proliferation of human lung fibroblasts and Sun et al (11) indicated that miR-186 regulates the formation of tumor-related fibroblasts. In addition, Cui et al (10) revealed that miR-186 inhibits the proliferation and metastasis of non-small-cell lung carcinoma cells by targeting Rock1.…”
Section: Discussionmentioning
confidence: 99%
“…miR-186 is one of the most studied miRNA molecules, and it regulates the apoptosis, proliferation and autophagy of various types of tumors (10)(11)(12)(13). However, few reports have been published regarding the effect and mechanism of action of miR-186 on bladder cancer (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The Genome Data Viewer NCBI database (build 37) locates 52 different genes along the fragile region ( Figure S1), with many of these genes regulating important cellular functions; a long non-coding RNA is also present (LINC01360), as well as a microRNA (miR186) known to function as a tumor suppressor in several solid tumors [33]. An 886 kb long gene, NEGR1 (neuronal growth regulator 1) is also present in the region, underscoring the previously reported association between long genes and CFSs instability [34].…”
Section: Molecular Characterization Of 1p311 Fragile Sitementioning
confidence: 99%
“…miR-186 in CAFs is involved in glycolysis, and combined with the 3′-untranslated region of its target gene glucose transporter 1 (Glut 1), it is active in regulating the uptake of glucose and production of lactate (106). The roles of CAFs in cancer glucose and energy metabolism are recognized using a novel method named the ‘reverse Warburg effect’ (23,107,108).…”
Section: Epigenetic Alterationsmentioning
confidence: 99%